Relations between coping skills, symptom severity, psychological symptoms, and quality of life in patients with irritable bowel syndrome - Farnaz Torkzadeh; Manizheh Danesh; Leila Mirbagher; Hamed Daghaghzadeh; Mohammad Hassan Emami (International Journal of Preventive Medicine, 2019)
Background: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders with significant impact on quality of life (QOL). Considering the role of stress in the clinical course of IBS, we investigated associations between stress coping skills and symptoms and QOL in IBS patient. Methods: A cross-sectional study was conducted on 95 IBS patients referring to tertiary care centers. Coping skills (Jalowiec coping scale), IBS symptom severity scale, disease-specific QOL (IBS-QOL), and symptoms of depression and anxiety (Hospital Anxiety and Depression Scale [HADS]) were evaluated by questionnaires. Bivariate and multivariate analyses were performed to investigate association among these parameters. Results: Disease severity was positively correlated with emotive (r = 0.30) and fatalistic (r = 0.41) and negatively correlated with optimistic (r = −0.25) and confrontive (r = −0.24) coping strategies. Psychological dysfunction (total HADS score, B [95% (confidence interval) CI] = 2.61 [0.001–5.21]) and fatalistic coping (B [95% CI] = 35.27 [0.42–70.13]) were significant predictors of IBS severity. Conclusions: However, IBS patients involved in this study utilized adaptive coping strategies more frequently. Our study showed that use of maladaptive coping strategies had positive correlation with symptom severity and degree of anxiety and depression among patients, while implementation of optimistic strategies were found to be negatively correlated to severity of symptoms and also utilization of adaptive coping styles was associated with lesser degree of anxiety and depression.